PEMBERITAAN HUMAN TRAFFICKING (PERDAGANGAN MANUSIA) DALAM SURAT KABAR ELEKTRONIK DI LIMA NEGARA ASEAN Human Trafficking News on On-Line Media in Five Countries in ASEAN - Fauziah, A Fauziah Astrid (KAREBA : Jurnal Ilmu Komunikasi, 2011)
This study aims to analyze the portion of the human trafficking problem in the Asean on electronic newspapers in the five Asean countries, media attention to the online human trafficking problem in the five Asean countries, and the role of media in five countries of the Asean Human Trafficking issues. Research was conducted through online media in the five Asean countries for more than three months by using the method of quantitative descriptive content analysis and discourse as research procedures that produce descriptive data from the analytical results of the study and analysis of the content library. Selection technique using the information on the sampling technique in the period July-December 2006 and are determined based on certain criteria that are based on the purpose of research. Results of research shows that 1) the portion of the information provided online media in every country of Asean, was much larger than provided by the TJP with other media, and even MST provide at least a portion, 2) media attention to the issue online human trafficking, as well as greater given by TJP although there are some things to exclusion, 3) The role of online media for issues related to human trafficking is on the portion of the system and the attention and the press that they thought. In general, TJP run more functions and role as agents of social control and change